Análise da dor em injeções intravítreas - Pereira, Carlos Eduardo Gonçalves (2021)
Intravitreal injections became an important treatment for many ophthalmological diseases. Antibiotics, antiangiogenics, steroids, antifungal medications can be delivered directly to the vitreous cavity. As the number of procedures rise worldwide, and some individuals require monthly injections, it is critical to study the pain involving the injections. The objective of this study was to determine the incidence and degree of pain during intravitreal injections. We also studied the influence of age, medication injected, disease treated, previous cataract surgery, number of applications, influence of expected pain and needle size. 201 intravitreal injections were realized in 2019, performed by the same surgeon following the same technic in all procedures. The pain was assessed by the numerical pain scale, administered verbally. After statistical analysis we found an incidence of pain of 72,1%, bigger needles had a statistically higher incidence of pain. The intensity of pain was mild, and all the studied variables showed no statistically significant difference.